Aligning Software Architecture with Cost Structure: A Comparative Study Using ATAM and Lean Canvas in Early Startup Development - Fadhillah, Jan Falih; Kusumo, Dana Sulistiyo (Informatika, Universitas Jenderal Soedirman, 2025)
Startups in the early phase often face challenges in balancing operational efficiency with resource constraints. This research find how startups can choose software architecture to align with cost structures with the Lean Canvas framework and the Architecture Trade-off Analysis Method (ATAM). Lean canvas allows for startups to identify cost structures at an early stage and align with market demands efficiently and ATAM helps to evaluate software architecture systematically by analysing trade-offs and quality attributes. Although microservice architecture offers modularity and scalability, its implementation can lead to higher operational costs making it unsuitable for startups with limited budgets. On the other hand, monolithic architecture is more cost-effective, easy to manage and suitable for the needs of early-stage startups. This research emphasizes that systematic evaluation of software architecture based on business goals and resource limitations is essential for startup growth for sustainability. By combining Lean Canvas for business validation and ATAM for architectural decision making, startups can optimize operational and technical strategies, analyse risks, and identify trade-offs that are implemented according to business development.